Analisis Pemetaan Industri Kreatif Subsektor Kerajinan Serta Dampak Peningkatkan Kesejahteraan Masyarakat di Kabupaten Aceh Besar - Nasir Nasir; Yuslinaini Yuslinaini (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2017)
This study aims to look at the development of the Creative Industries in particular subsector of crafts as well as to see the extent of the impact of the increase in equality communities in Aceh Besar district, by mapping the creative industries subsector Kerajiana in Aceh Besar district, this sample began with four (4) sub-district where other districts will be further research, this research activity used a qualitative approach with descriptive type in this case does not isolate individual or organization into variables or hypothetical, but sees it as part of a wholeness. Data analysis technique used is descriptive qualitative and quantitative methods by using a simple statistical formula and SWOT analysis to determine product competitiveness strategy with SWOT Matrix qualitative matrix. The results showed that the craft industry subsector in 4 (four) districts in Aceh Besar district has a strategic role in improving social welfare and reduce unemployment. It can be seen from the absorption of labor in the handicraft industry in each sub-district in Aceh Besar.